How do cities and regions adapt to socio-economic crisis? Towards an institutionalist approach to urban and regional resilience - Lang, Thilo (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
This paper depicts resilience as a systemic ‘adaptive capacity’ to cope with social and economic crisis situations at the urban and regional level. It argues that the notion of resilience has to be conceptualised in such a way that processes of and (institutional) frameworks for decision making are recognized. Such an understanding suggests a new institutionalist approach to governance may be useful, one highlighting dominant norms, perceptions and paradigms leading to particular forms of action. Under the axiom of a socially constructed world the benefit of the notion of resilience as an analytical tool in urban and regional studies lies in a better understanding of change in complex systems of socio-spatial interdependencies. It thus has the potential to fill a gap in new institutional theory and contemporary governance research.
Keywords: Resilience; Urban and regional development; Economic crisis; Governance; New institutional theory